Caracterização por espectroscopia Raman do endocarpo de babaçu tratado termicamente - Ocaris, Enrique Ronald Yapuchura (2014)
This work deals with the characterization by Raman spectroscopy of the endocarp of babassu coconut (a native biomass in the Northeast and Central Brazil) subjected to heat-treatment temperatures (HTT) between 800 and 2200° C with intervals of 200° C. We have also samples heat treated at lower temperatures (200, 400 and 650 ºC) that allowus to observe theinitial structural evolution of the material. During the carbonization process, which involves heat treatment of the samples in an inert atmosphere, large structural changes in the studied carbon material (which is non-graphitizable) are produced. The used tool in this work to observe these changes is Raman spectroscopy. This technique has allowed determining thein-plane average size Laof the graphite-like crystallites of the materialfor graphitizable and graphitic carbons such as nanografites, and evaluatingthe crystallinity and the structural defects.Two different laser excitation energies (EL) were used: 532 nm (2,33 eV) and633 nm (1,96 eV).The Ramanspectra ofall samples of heat treated endocarp of babassu coconutpresent the bands Dand Gcharacteristics of carbonaceous materials. The dispersivebehavior of theDbandwas observed, wherethe frequency ofmaximumintensityvarieswhen changingthelaserexcitation energy.Such behavioris the oppositeof that observedin theGband, whichexhibits anon-dispersivebehavior.TheDand G bandshavebroadpeaksfor the sampleswith lowHTT. With increasingHTTthe widthsof the peaksDand Gdecrease andthe linesbecomes more prominent due tocarbonizationprocess.Thiscarbonization that occurswith asignificant growthofthe graphite-likecrystallites of the materialis evidencedby the appearanceof theG'band. TheG’ band can be seenmore clearlyin the spectraobtainedwith the532 nmlasersourcewithHTTsamplesfrom1800 °C.Withthe lasersource of633nmtheG'bandis onlyobservedin the samplewithHTTof 2200ºC.Insamples from the withHTTof2000 °Cthe presenceof theD’bandisobserved, as well as otherminor peaks(2D', D+G,and T+D).Measurements of Lavalues for the samples with HTT between 800 and 2200°C obtained with x-ray diffraction were used to verify the linear relationship (developed by Cançado et al. for nanografites) between Laand the inverse of the ratio of integrated intensities of the Raman bands Dand G(ID/IG)taking into account the laser excitation energy. It was observed that the dependence of Laon the laser excitation energy, as suggested by Cançado et al., was fundamentalin putting the Raman measurements obtained at different laser energies in the same curve. However thestraight lineof (????????)????4as a function of 1/????with the best correlation coefficient for the heat-treated endocarp of babassu coconut does not pass through the origin as in nanografites. Our results indicate that for non-graphitizable carbons such as the heat-treated endocarp of babassu coconut the expression of Cançado et al. require the addition of a negative constant term (a linear coefficient)in the straight line of (????????)????4as a function of 1/????.The new obtained expression indicated that the maximum size of the crystallite size Lafor heat treated endocarp of babassu coconut is of the order of 11 nm, which is compatible value fora non-graphitizable material. It would be important that future works with other materials could check the results here obtained, including the values of the obtained constants (angular coefficient and linear coefficient of the fitting).Raman lines due to the presence of structures containing Silicon in the materialwere also observed.In the HTT of 800°C we have regions of the sample with a line associated with the presence of SiO2, while in In the HTT of 2000°C we have a line associated with the presence of SiC.This occurs isbecause the endocarp of babassu contains SiO2in the mineral matter (ashes), which is transformed into SiCfrom HTT of 1200°C, as it is verified with other techniques. The Raman lines due to the presence of silicon (in the form of SiO2or SiC) are not observed in all spectra, because the structures containing silicon are not evenly distributed throughout the material from the microscopic point of view, as it is detailed in a mapping of the sample with HTT of 800°C. Thestructural changes involving silicon studied with Raman Spectroscopy will be reported in more detailsin future works.